Transformation of motion and force flow in drive mechanism with minimal side reaction in the translational pair - P. D. Balakin; I. P. Zgonnik (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The possibility of creating a circuit solution of a mechanical system with a minimum value of the lateral response in a resource-determining translational pair is proved. To solve this problem, the fundamental position of mechanics about the addition of the motion of a rigid body is used and it is proved that with the recommended proportions of the kinematic dimensions of the drive links, the trajectory of the pin of the crank being a hypocycloid degenerates into a straight line, which provides the necessary power properties of the kinematic chain of the mechanical drive